Anti-biofilm effect of egg white ovotransferrin and its hydrolysates against Listeriamonocytogenes. (1st August 2022) - Cho, Hee Yeon; Lee, Ji-Eun; Lee, Jae Hoon; Ahn, Dong Uk; Kim, Kee-Tae; Paik, Hyun-Dong
Abstract: Listeria monocytogenes is a major foodborne pathogen that causes listeriosis and poses potential threats to human health. Ovotransferrin (OT) is an egg white protein with many functional properties. In this study, the anti-biofilm effect of OT and OT hydrolysates (OTH) of enzymes (bromelain, Flavourzyme®, Neutrase®, papain, and Protamex®) against L. monocytogenes was investigated. The OTH prepared with bromelain (OTBM), Flavourzyme® (OTFV), and papain (OTPP) significantly inhibited the biofilm formation of L. monocytogenes strains. The OTFV and OTPP showed higher biofilm eradication activities than the OT, with the maximum activity (48.61–74.43%, 40.89–67.75%, and 37.51–61.07% in L. monocytogenes ATCC 15313, H7962, and NADC Scott A, respectively) found in the OTPP. The L. monocytogenes treated with the OTPP exhibited decreased cell surface hydrophobicity, auto-aggregation, exopolysaccharides production, biofilm metabolic activity, and the expression of genes ( actA, agrD, dltB, flaA, flgE, and prfA ) related to the biofilm-forming activity of L. monocytogenes . The biofilm formation of L. monocytogenes on glass coupon was significantly inhibited by the OT and OTPP treatments. These results suggested that the OT and OTH, especially the OTPP, exerted anti-biofilm effects against L. monocytogenes . Therefore, OTPP could be used as a potential natural anti-biofilm agent to control food poisoning in the food industry. Highlights: Ovotransferrin (OT) and its hydrolysates the reduced biofilm formation of L. monocytogenes. OT hydrolysate prepared with papain (OTPP) inhibited cell characteristics, EPS production, and biofilm metabolic activity. OTPP downregulated the expression level of biofilm-related genes in L. monocytogenes. OTPP could be used as a natural anti-biofilm agent to control food poisoning in the food industry.